Providing on-line support to families of people with brain injury and challenging behaviour: A feasibility study. Issue 3 (16th March 2021) - McDonald, Skye; Trimmer, Emily; Newby, Jill; Grant, Samantha; Gertler, Paul; Simpson, Grahame K.
ABSTRACT: Challenging behaviour following traumatic brain injury (TBI) is a major source of stress for families. Providing support can be limited by availability of clinicians and geographic location. A solution is to provide support on-line. This study aimed to evaluate the feasibility of an on-line treatment programme "Carer's Way Ahead" that provides families and carers with psychoeducation about TBI and challenging behaviours, specific approaches to managing apathy, irritability/aggression, acting without thinking and social difficulties and also self-care for the family member. Each module was supplemented with detailed notes and summaries of the sessions. Six family carers, five caring for a person with TBI and one caring for a person with stroke, worked through the programme, providing feedback on wording, content, structure and useability. They also completed measures of family functioning, social problem solving, carer strain, mood and the nature and severity of challenging behaviours. In general, the families were positive about the programme with most finding it useful, practical and logically structured although not all believed it was helpful. There was little change in self-reported challenging behaviour, mood, carer strain and family function over the few months of the programme. Longer-term effects were not examined but this requires further research.